The rational roots of the given equation are -4, -1, 2
Solution:
Given, equation is:
![x^(3)+3 x^(2)-6 x-8=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/paxxkkabrnsykt784sreqiu82jxbw8gic7.png)
We have to find the rational root of the given cubic equation.
Now, let us try it by trail and error method.
So, put x = 1 in given
![\begin{array}{l}{\rightarrow(1)^(3)+3(1)^(2)-6(1)-8=0} \\\\ {\rightarrow 1+3-6-8=0} \\\\ {\rightarrow 4-14 \\eq 0} \\\\ {\rightarrow \text { So } 1 \text { is not a solution }}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k17f4rv0t523o65z9b2u0e2ohyzm4isrzh.png)
![\begin{array}{l}{\text { Now, put } x=2} \\\\ {\rightarrow(2)^(3)+3(2)^(2)-6(2)-8=0} \\\\ {\rightarrow 8+12-12-8=0} \\\\ {\rightarrow 20-20=0} \\\\ {\rightarrow 0=0} \\\\ {\text { So } 2 \text { is an solution of the given equation }}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vd4dlyxo54v1kttmngexrhpm7aa40wxvky.png)
![\begin{array}{l}{\text { Now, put } x=-1} \\\\ {\rightarrow(-1)^(3)+3(-1)^(2)-6(-1)-8=0} \\\\ {\rightarrow-1+3+6-8=0} \\\\ {\rightarrow 9-9=0} \\\\ {\rightarrow 0=0} \\\\ {\text { So }-1 \text { is also solution }}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fn2bbs6ddncx7k510gv3l17j82xkilyjdx.png)
Now we have got two roots 2 and – 1
We can find the third root by formula sum of roots
![\text {Sum of roots }=\frac{-x^(2) \text { coefficient }}{x^(3) \text { coefficient }}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uh75oog0h3dct3xci6z8z3oa2s94ibb408.png)
![\begin{array}{l}{2+(-1)+3^{\text {rd }} \text { root }=(-3)/(1)} \\\\ {\rightarrow 2-1+3^{\text {rd }} \text { root }=-3} \\\\ {\rightarrow 3^{\text {rd }} \text { root }=-3-1} \\\\ {\rightarrow 3^{\text {rd }} \text { root }=-4}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jqj5y4y2v3t1mndzlsrx71vnzqgdvvwsc7.png)
Hence, the rational roots of the given equation are -4, -1, 2